The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.chiabu.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Welfare recipients’ involvement with child protective services after welfare reform

Abstract: Objective-This study identifies factors associated with child protective services (CPS) involvement among current and former welfare recipients after welfare reform legislation was passed in the US in 1996.Method-Data come from the Women's Employment Study, a longitudinal study of randomly selected welfare recipients living in a Michigan city in 1997 (N = 541). In order to identify risk factors for CPS involvement among current and former welfare recipients, multinomial logit analyses with 29 independent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Our reliance on self‐reports of CPS involvement is consistent with other analyses that have used large population‐based samples (Nam, Meezan, & Danziger, ). Nonetheless, an important concern is that respondents may underreport.…”
Section: Methodssupporting
confidence: 83%
“…Our reliance on self‐reports of CPS involvement is consistent with other analyses that have used large population‐based samples (Nam, Meezan, & Danziger, ). Nonetheless, an important concern is that respondents may underreport.…”
Section: Methodssupporting
confidence: 83%
“…A potential limitation of this study is that, similar to some prior research that also used large representative samples of families (e.g., Berger et al, 2009; Nam et al, 2006; Zolotor et al, 2008), CPS involvement is based on maternal self-report rather than administrative (or at least independent) data. Administrative or independent report of CPS involvement is not available in the FFCWS.…”
Section: Discussionmentioning
confidence: 99%
“…The variable for CPS involvement was based on the question, “Since the child was born, has Child Protective Services contacted you about any child or children in this household?” (0= no , 1 = yes ). Following precedent established by other researchers (Berger, Paxson, & Waldfogel, 2009; Nam, Meezan, & Danziger, 2006), these families were considered to be CPS involved (e.g., to have been investigated or assessed by CPS) because CPS is unlikely to contact a family regarding a “screened-out” child maltreatment report. For those who indicated having had CPS involvement, a subsequent question asked the month and year of the most recent CPS contact.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, because no existing national, longitudinal survey includes both income data and administrative data on CPS involvement, self-reports are commonly used in population-based studies (Berger et al, 2009; Lee et al, 2014; Nam et al, 2006; Slack et al, 2011). Prior research documents consistency in the predictors of both self-reported and administratively documented CPS involvement, as well as in the magnitudes of association between these predictors and each measure (Slack et al, 2011).…”
Section: Data and Measuresmentioning
confidence: 99%